2010
DOI: 10.1111/j.1600-0447.2010.01553.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a multifaceted intervention to limit excessive antipsychotic co‐prescribing in schizophrenia out‐patients

Abstract: These data suggest that changes of TDP-43 in ALS skin are likely to be related to the disease process and that metabolic alterations of TDP-43 may take place in the skin of patients with ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…When delivered with additional intensive training, academic detailing reduced use of antipsychotics among elderly nursing home residents (15). In contrast, a recent study found that four inperson educational visits did not reduce antipsychotic polypharmacy in a Danish municipality, but the meetings were poorly attended (16). …”
Section: Strategies To Improve Quality Of Prescribingmentioning
confidence: 95%
“…When delivered with additional intensive training, academic detailing reduced use of antipsychotics among elderly nursing home residents (15). In contrast, a recent study found that four inperson educational visits did not reduce antipsychotic polypharmacy in a Danish municipality, but the meetings were poorly attended (16). …”
Section: Strategies To Improve Quality Of Prescribingmentioning
confidence: 95%
“…Never say never to polypharmacy ⁄ combinations Rank and file psychiatrists seem to have ignored the call for Ôalways say monotherapyÕ as the data show that antipsychotic polypharmacy ⁄ combination use is growing and is higher than ever, overtaking monotherapy (11), and seemingly impervious to educational and administrative interventions to reduce polypharmacy (12,17). Although some believe these trends reflect substandard care, the shift toward more antipsychotic polypharmacy ⁄ combinations may actually be due to something else, namely, the growing gap between evidence-based practice and practicebased evidence, at least for certain patient populations receiving antipsychotics.…”
mentioning
confidence: 99%
“…The Danish Schizophrenia Registry is the only Danish nationwide registry that contains a measure of functional ability (GAF-F), which is not the case for other Danish registries because they are structured around collection of data with an administrative purpose. Among others, an intervention study to reduce the frequency of antipsychotic polypharmacy used GAF-F data from the registry to characterize the subjects in the intervention and control area regarding functional abilities 7. A recent study documented that quality of care improved with the implementation of the registry and the systematic monitoring program, but also that a high degree of variation between the hospitals remains 8…”
Section: Examples Of Researchmentioning
confidence: 99%